(untitled) (Zoo Botanica, 2025)
The identification and evaluation of genetically diverse and high-performing genotypes under varying environmental conditions is essential for developing stable and high-yielding rice varieties. This research aimed to assess the genetic variation among twenty-two (22) open-pollinated candidate and two (02) control varieties of fine rice for paddy yield, yield related traits, kernel quality, and resistant against insects and diseases grown at eight locations in National Uniform Yield Trials (NUYT) during 2019. Results revealed that genotypes EFLD, GC-75 and KSK-111-H produced the highest average paddy yields of 4039 kg ha-1, 3980 kg ha-1 and 3928 kg ha-1, respectively and stayed statistically at par with each other. Genotype P-35 exhibited the maximum plant height (134.2 cm), while genotype PK-1121-Aromatic gave the highest tillers count per plant (15.7). Maximum length of panicle (30.1 cm) and grains count per panicle (121.0) were noted in genotype KSK-111-H. Genotype SRI-23 displayed the maximum 1000-grain weight (30.7 g), but it also took maximum days to achieve maturity. Highest paddy yield was recorded at the locations Bahawalnagar and Faisalabad, while lowest yield was documented at DI Khan. Genotypes 52-S and EFLD exhibited the highest recoveries of brown rice (85%) and head rice (62%), respectively. Maximum grain length (9.96 mm) and cooked grain length (18.6 mm) were measured in genotype SRI-23, while highest bursting (25%) was noted in genotype KSK-111-H. Most of the genotypes showed resistance against stem bore and leaf folder, whereas half of the genotypes were susceptible against bacterial blight disease. Based on these outcomes, genotypes EFLD, GC-75 and KSK-111-H could be recommended for general cultivation in order to achieve the highest paddy yield.